2007
DOI: 10.1080/12538078.2007.10516050
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids and tocochromanol patterns of some Turkish Apiaceae (Umbelliferae) plants; a chemotaxonomic approach

Abstract: Abstract.-The plant family Apiaceae is known to produce a set of unusual fatty acids in the seed oils. The fatty acids and tocochromanols contents of some species of Prangos, Ferulago, Heracleum, Conium and Malabaila from Apiaceae are determined and analysed by GC, GC-MS and HPLC. Some of the studied species are endemic to Turkey. Petroselinic acid (18:1Δ6c) is the predominant constituent and consisted of more than half of the oil. Linoleic acid is the second highest fatty acid component. There is very little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Vicia peregrina had the lowest level of saturated acid and V. angustifolia had the highest amount of saturated fatty acid (SFA) concentration (Table 1). on the other hand, the unsaturated fatty acid composition of the Vicia species was determined at levels as high as those reported for other family members of the Vicia species (Pastor-Cavada et al, 2009a), Fabaceae (Bagci et al, 2004a), Lamiaceae (Bagci, 2007), Boraginaceae (Bagci et al, 2004b), Apiaceae (Bena et al, 1998) (Bakoglu et al, 2009).…”
Section: Resultsmentioning
confidence: 89%
“…Vicia peregrina had the lowest level of saturated acid and V. angustifolia had the highest amount of saturated fatty acid (SFA) concentration (Table 1). on the other hand, the unsaturated fatty acid composition of the Vicia species was determined at levels as high as those reported for other family members of the Vicia species (Pastor-Cavada et al, 2009a), Fabaceae (Bagci et al, 2004a), Lamiaceae (Bagci, 2007), Boraginaceae (Bagci et al, 2004b), Apiaceae (Bena et al, 1998) (Bakoglu et al, 2009).…”
Section: Resultsmentioning
confidence: 89%
“…Gas chromatography (GC) fingerprinting of the FAs composition is a valuable tool in chemotaxonomic studies . Several studies clearly have confirmed the chemotaxonomic relationships between angiosperm families, such as Boraginaceae , Cannabaceae , Lamiaceae , Apiaceae , Rubiaceae , Malvaceae , and Vitaceae by evaluating the patterns of the FAs composition. There are a few studies that have been focused on the chemotaxonomic importance of the FAs composition in Salvia seed oils .…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by many observations of insect herbivory on G. lucida and very few of mammalian browsing (see Other biotic and abiotic roles, below). G. lucida also produces the fatty acid petroselinic acid but lacks proanthocyanidins and ellagic acid, features which have been useful in taxonomic classification (Bagci 2007).…”
Section: Chemistrymentioning
confidence: 99%